2017
DOI: 10.14430/arctic4631
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Injuries from Line Entanglements, Killer Whales, and Ship Strikes on Bering-Chukchi-Beaufort Seas Bowhead Whales

Abstract: We analyzed scarring data for Bering-Chukchi-Beaufort (BCB) Seas bowhead whales (Balaena mysticetus) harvested by Alaska Native hunters to quantify the frequency of line entanglement, ship strikes, and killer whale-inflicted injuries. We had 904 records in our database for whales landed between 1990 and 2012, and after data quality screening, we found 521 records containing information on scarring. Logistic regression was used to evaluate different combinations of explanatory variables (i.e., body length, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 22 publications
(40 reference statements)
3
56
1
Order By: Relevance
“…) were assigned to the scar data set for landed whales (George et al . ) we found that about 49% (11 of 33) of the whales over 50 yr old carried entanglement scars.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…) were assigned to the scar data set for landed whales (George et al . ) we found that about 49% (11 of 33) of the whales over 50 yr old carried entanglement scars.…”
Section: Discussionmentioning
confidence: 63%
“…Our scar acquisition rate estimate therefore applies mainly to adult whales, based on an average length‐at‐maturity for both sexes whose range is approximately 12–13.7 m (Koski , George et al . ). When estimated ages (Wetzel et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations